Analisis Strategi Pemasaran Melalui Live Tiktok dalam Meningkatkan Minat Konsumen Ditinjau Menurut Perspektif Ekonomi Islam (Studi Kasus Toko Perabot Sibuhuan) - Aminah Lubis; Sairin Hutasuhut; Nur Jannah Nasution (Dirosah Islamiyah, 2026)
This study aims to determine the marketing strategy through TikTok live broadcasts to increase consumer interest at the Sibuhuan Furniture Store and analyze its application from an Islamic economic perspective. This study used a qualitative method with a descriptive approach. The research subjects consisted of the owner, employees, and consumers directly involved in the TikTok live broadcast marketing activities. The object of the study was the marketing strategy implemented to increase consumer interest based on Islamic economic principles. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results show that the TikTok live broadcast marketing strategy proved effective in attracting consumer interest through direct interaction, detailed product explanations, a communicative broadcast atmosphere, and special promotions during the live broadcast. This creates emotional closeness, a sense of trust, and is able to increase sales. From an Islamic economic perspective, the implemented strategy reflects the values of honesty (shidq), justice ('adl), trustworthiness (amanah), and transparency in conveying product information. Businesses avoid fraud and prioritize blessings in transactions. Thus, marketing through TikTok live broadcasts is not only economically effective but also aligns with the principles of Islamic business ethics.